A multicriteria experimental analysis of impact on fiber reinforced polymer composite laminates. (September 2015) - Alemi-Ardakani, M.; Milani, A.S.; Yannacopoulos, S.; Shokouhi, G.
Graphical abstract: Highlights: A multicriteria-based experimental approach applied to impact optimization of FRPs. Kinking/brittle crack yielded high energy absorption in long-fiber laminates. Drop tower impact data correlated to post-impact bending and micro-tomography tests. Different fiber architectures resulted in conflicting impact performance measures. Abstract: The use of fiber reinforced polymers (FRPs) is rapidly increasing in air, land, and marine manufacturing sectors. This is despite the fact that a universal methodology has not been yet developed to assist designers in selecting optimum reinforcing fiber architectures under different loading scenarios. The focus of the present article is to recommend a systematic approach for selecting the architecture of long-fiber fabric reinforcements in FRP composite structures under impact events. Namely, nine design criteria were selected and quantified for four types of PP/glass laminates through drop tower impact testing under 200 J energy, four-point flexural bending before and after impact, as well as microtomographic damage analysis of impacted samples. Subsequently, ranking of the candidate laminates was found using a multiple criteria decision making (MCDM) technique to aid in selecting the overall best performing fiber reinforcement option under the presence of conflicting and inter-dependent design attributes.